ระบบวิเคราะห์ผลการทดสอบแรงดันอิมพัลส์แบบดิจิตอลสำหรับหม้อแปลงไฟฟ้ากำลัง : รายงานผลการวิจัย - วีระพันธ์ รังสีวิจิตรประภา (จุฬาลงกรณ์มหาวิทยาลัย, 1995)
A digital impulse analyzing system for the BIL test on power transformers is developed to check the generating impulse voltage waveform, i.e., the front time, tail time, chopped time, magnitude of voltage, and percent overshoot. The applied test voltage, obtained from the impulse generator, is measured by impulse voltage divider and the current flowing through the winding under test is measured by means of a resistive shunt. These analog signals are attenuated and changed to digital signals by a high frequency digital oscilloscope. These digital datas are then processed by a developed program. The results from the analysis of the characteristics of the measured voltage are displayed on the monitor of a microcomputer and the data is saved in diskettes which can be later used. The developed system was tested by performing BIL test on power transformers according to the TIS standard and other international standards. The analyzed results of the tests give a satisfactory accuracy.